The effect of fixation type on the survivorship of contemporary total knee arthroplasty in patients younger than 65 years of age: a register- based study of 115,177 knees in the Nordic Arthroplasty Register Association (NARA) 2000–2016 - Niemeläinen, Mika J; Mäkelä, Keijo T; Robertsson, Otto; Dahl, Annette W-; Furnes, Ove; Fenstad, Anne M; Pedersen , Alma B; Schrøder, Henrik M; Reito, Aleksi; Eskelinen, Antti (Acta Orthopaedica, 2020)
Background and purpose — Cemented fixation is regarded as the gold standard in total knee arthroplasty (TKA). Among working-age patients, there has been controversy regarding the optimal fixation method in TKA. To address this issue, we conducted a register-based study to assess the survivorship of cemented, uncemented, hybrid, and inverse hybrid TKAs in patients aged < 65 years. Patients and methods — We used the Nordic Arthroplasty Register Association data of 115,177 unconstrained TKAs performed for patients aged < 65 years with primary knee osteoarthritis over 2000–2016. Kaplan–Meier (KM) survival analysis with 95% confidence intervals (CI) and Cox multiple-regression model with adjustment for age, sex, and nation were used to compare fixation methods in relation to revision for any reason. Results — The 10-year KM survivorship of cemented TKAs was 93.6% (95% CI 93.4–93.8), uncemented 91.2% (CI 90.1–92.2), hybrid 93.0% (Cl 92.2–93.8), and inverse hybrid 96.0% (CI 94.1–98.1). In the Cox model, hybrid TKA showed decreased risk of revision after 6 years’ follow-up compared with the reference group (cemented) (hazard ratio [HR] 0.5 [CI 0.4–0.8]), while uncemented TKAs showed increased risk of revision both < 1 year (HR 1.4 [1.1–1.7]) and > 6 years’ (HR 1.3 [1.0–1.7]) follow-up compared to the reference. Interpretation — Both cemented and hybrid TKAs had 10-year survival rates exceeding 92–>93% in patients aged < 65 years. Cemented TKA, however, was used in the vast majority (89%) of the operations in the current study. As it performs reliably in the hands of many, it still deserves the status of gold standard for TKA in working-age patients.